ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RGEC PADA BANK BANTEN TAHUN 2011-2016 - DIDIN RASYIDIN WAHYU (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2018)
Abstract This study aims to find out how the health level of Banten Bank by using the RGEC method (Risk Profile, Good Corporate Governance, Earning, Capital) in 2011-2016. The type of research used is a descriptive research with a qualitative approach. Descriptive research design was created to describe the problem in a narrative manner supplemented with description of the bank’s health analysys qualitative research data. Variable and measurements in this study consist of Risk Profile, Good Corporate Governence, Earning, and Capital factor. Risk profile factor that assessed through the NPL and LDR ratios as a whole describe risk management that has been carried out fairly well. Good Corporate Governence factor of Banten Bank already has and implement corporate management very well. Earning or Profitability factor which is consist of ROA and NIM ratios. On average of ROA ratio of Banten Bank loses every years but the ratio of NIM is categorized as very well. The increase in the percentage of NIM illustrates an increase in managements ability to manage its productive assets in generating net interest income. By using the CAR indicator, researcher prove that Banten Bank has a good Capital factor which is above regulation of the Indonesian Bank namely 8%. This indicates that Banten Bank is able to finance operational activities and contribute sufficiently to profitability. The result of this analysis show that the soundness of Banten Bank in 2011-2016 which is measured using the RGEC method as a whole can be said to be a healthy bank.